INDUKSI MUTASI BIJI LADA PADA LD₅₀ DENGAN MUTAGEN KIMIA EMS - Puji Astuti; Asnawati Asnawati; Iman Suswanto (Fakultas Pertanian, Universitas Janabadra, 2024)
Pepper (Piper nigrum L.) is a spice plant that can be used as a kitchen ingredient for flavoring dishes and can also be used as a vegetable pesticide, medicine and even perfume. This study aims to determine the potential mutations that occur in LD₅₀ chemical mutagen EMS concentration of 0.3% against pepper seeds. This research was conducted in Limbung Village, Sungai Raya District, Kubu Raya Regency, West Kalimantan. This research took place from August 23 to November 20, 2023. This research uses an experimental method that is carried out descriptively using an environmental design, namely a complete randomized design (RAL). The total pepper seeds used were 250 seeds, namely 200 pepper seeds treated with 0.3% EMS mutagen (LD₅₀) and 50 pepper seeds without treatment (control) which were used as a comparison. The variables observed in this study were germination percentage (%), sprout appearance (score), leaf color, leaf shape (leaf blade shape, leaf tip shape, leaf base shape, leaf recurrence shape and leaf surface), stem color, stem shape and root length (cm). The results showed that the effect of using 0.3% EMS mutagen is thought to have the potential to increase variation in leaf blade shape, leaf tip, leaf color, stem color and stem shape and root length. However, it did not show the potential for mutation in the shape of the leaf base and leaf surface.